Effectiveness of design joint-studio implementation in architecture education - Zavari, Sara (2016)
Architectural education is based primarily around the design studio as a pivot and gathering point of all knowledge and skill accreted throughout the curriculum; there is no simple answer or given approach to architectural pedagogy but a continuous routine framework. Delahaye in 2005 mentioned, Design studios universally apply the semistructured project base learning strategy. Simple investigation on current publications in design Joint-Studios reveals a lack of how such an evolutionary education pedagogical framework processes took place in Malaysia therefore the research aim is to improve our knowledge base and quality of architecture education; because while the current design studio may represent the best teaching ideas for this profession yet they are not without problems. To address this objective and increase the particularities the research involves the design Joint-Studio of the 3rd year architecture design studio of UPM (University Putra Malaysia, Malaysia) and 3rd year architecture design studio of UIN (Islamic State University of Malang, Indonesia) for one semester with total number of 72 students; Two empirical studies are carried out with the intention of investigating lecturers‟ and students‟ perceptions and expectations from Design Studios and Design Joint-Studios. Base on this study it was found that the aspects of design studios like studio pedagogy, culture, and technology are limited and in terms of the future, a more comprehensive approach is needed.